2018
DOI: 10.1177/0033294118787496
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy as a Mechanism Linking Daily Stress to Mental Health in Students: A Three-Wave Cross-Lagged Study

Abstract: Background and Objectives While stress is generally well established to be predictive for different indicators of mental health, little is known about the longitudinal effects of daily life stressors and the role of self-evaluation factors. We tested whether perceived general self-efficacy is a mediator for the association between daily life stressors and psychopathological symptoms as well as subjective well-being. Methods Data derived from 2160 Chinese university students was assessed at three time points wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
51
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 82 publications
9
51
0
10
Order By: Relevance
“…In accordance with this finding, self-efficacy among rescue workers was found to mediate the association between stress appraisal and compassion satisfaction [31]. Furthermore, general self-efficacy was found as a mediator for the association of daily life stressors with psychopathological symptoms and subjective well-being [32]. One possible explanation may stem from the Conservation of Resources (COR) theory [33,34] which proposes that individuals seek to build up and retain resources as a result of actual or threatened loss thereof, after coping with stressful circumstances.…”
Section: Discussionsupporting
confidence: 61%
“…In accordance with this finding, self-efficacy among rescue workers was found to mediate the association between stress appraisal and compassion satisfaction [31]. Furthermore, general self-efficacy was found as a mediator for the association of daily life stressors with psychopathological symptoms and subjective well-being [32]. One possible explanation may stem from the Conservation of Resources (COR) theory [33,34] which proposes that individuals seek to build up and retain resources as a result of actual or threatened loss thereof, after coping with stressful circumstances.…”
Section: Discussionsupporting
confidence: 61%
“…Besides, our results suggest that improving self-efficacy will help to alleviate the anxiety and depressive symptoms of medical staff during the COVID-19 outbreak. Manipulating self-efficacy is an important way to prevent mental health problems when dealing with stress ( Schönfeld et al, 2019 ). Previous studies have focused on the effects of self-efficacy on the mental health and work quality of medical staff ( Amiri et al, 2019 ; Tang et al, 2019 ), and it suggested that necessary interventions should be implemented to improve the self-efficacy of medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…However, a low level of self-efficacy harms a person’s psychological well-being ( Cieslak et al, 2008 ; Sachs-Ericsson et al, 2011 ). Importantly, studies have shown that self-efficacy is one of the critical factors that modulate an individual’s emotions, especially feelings of anxiety and depression ( Bandura et al, 1982 ; Kanfer and Zeiss, 1983 ; Cybulski et al, 2017 ; Schönfeld et al, 2019 ). These studies suggested that higher levels of self-efficacy are associated with lower levels of feelings of anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-efficacy refers to the individuals’ beliefs about their capability to produce given attainments and perform specific tasks [ 25 ]. People high in self-efficacy tend to deal effectively with a variety of stressful situations to achieve their goals [ 26 , 27 , 28 ]. Optimism refers to the generalized expectation of positive vs. adverse outcomes in essential domains of life [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%